Artbestämning och karaktärisering av laktosväxande vildjäst från Nigeria - Good, Johanna; Bellot Avendaño, Gelmy (My University, 2022)
During cheese production, whey is a residual product, containing disaccharide lactose and other nutrients and minerals. Large quantities of whey must be disposed of yearly, which becomes costly since it requires further processing. The possibility of using microorganisms to convert this cheap and available resource into valuable bioproducts is an attractive approach. However, few known yeasts can perform this task without extensive genomic engineering. The discovery of yeast species that naturally produce valuable biochemicals could increase the value of whey in the industry. Therefore, from a large collection of wild Nigerian yeast isolates, our research sought to identify new yeast species that can grow on lactose. This was done by identifying species with DNA sequence data from a collection of ~6000 wild Nigerian yeast strains, were ~230 was found to grow on lactose. One representative isolate from 15 selected species were chosen for cultivating, HPLC-analysis, and literature review. The species were selected based on findings in literature such as usage in industry, bioproduct formation and biohazard level. The selected species include Apiotrichum mycotoxinovorans, Candida orthopsilosis, Candida pseudointermedia, Clavispora lusitaniae, Cutaneotrichosporon curvatum, Cyberlindnera fabianii, Kodamaea ohmeri, Meyerozyma caribbica, Meyerozyma carpophila, Moesziomyces antarcticus, Papiliotrema flavescens, Rhodotorula mucilaginosa, Trichosporon insectorum, Vishniacozyma taibaiensis and Yarrowia lipolytica. The literature research of this study revealed that all yeast species may have industrial potential, but more research is needed, especially for C. pseudointermedia, M. carpophila and V. taibaiensis, for which information was lacking. Species that produced fatty lipids deemed of special interest, due to the potential for future use in biotechnology. The result from the cultivation showed that half of the species grew well on lactose medium, which was backed up by the HPLC analysis. M. antarcticus was the only species which had greater growth in lactose medium than in glucose medium, and which also, shown trough the HPLC analysis, produced products that differed from other species. Although a few species showed good potential, further research is needed to determine if the species is suitable future industrial usage.